Growth and yield of kale (Brassica oleracea var. Acephala) on different vermicompost dosages and plant spacings - Saraswati Kurnia Dewanti; Eny Fuskhah; Sutarno (Jurnal Pertanian Tropik, 2019)
This study aimed to examine the effect and interaction between vermicompost dosage and plantspacing on kale growth and yield. The research was held on March – June 2019 in Tegalsari,Sidomukti, Semarang Regency and at Ecology and Crop Production Laboratory, Faculty of Animaland Agricultural Sciences, Diponegoro University, Semarang. The study used a completelyrandomized factorial design 4 x 2 with 3 replications. The first factor was the vermicompost dosage of100 kg N/Ha (A1), 150 kg N/Ha (A2), 200 kg N/Ha (A3), and 250 kg N/Ha (A4). The second factorwas plant spacing of 20 x 40 cm (B1) and 30 x 40 cm (B2). Data were analyzed by variance andproceeded with DMRT test at level 5%. The observed variables were plant height, amount of leaves,chlorophyll, root length, fresh weight, and dry weight. The results showed that different dosages ofvermicompost and plant spacing only affected chlorophyll and root length of kale. The highestchlorophyll was attained at the treatment of 150 kg N/Ha vermicompost dosage and 20 x 30 cm plantspacing, equal to a treatment of 250 kg N/Ha vermicompost dosage and 30 x 40 cm plant spacing.The highest root length was attained at the treatment of 250 kg N/Ha vermicompost dosage and 30 x40 cm plant spacing, equal to the treatments of 100 kg N/Ha vermicompost dosage and 30 x 40 cmplant spacing and 200 kg N/Ha vermicompost dosage and 20 x 40 cm plant spacing.